Updated efficacy of avelumab in patients with previously treated metastatic Merkel cell carcinoma after ≥1 year of follow-up: JAVELIN Merkel 200, a phase 2 clinical trial. Issue 1 (19th January 2018) - Kaufman, Howard L.; Russell, Jeffery S.; Hamid, Omid; Bhatia, Shailender; Terheyden, Patrick; D'Angelo, Sandra P.; Shih, Kent C.; Lebbé, Céleste; Milella, Michele; Brownell, Isaac; Lewis, Karl D.; Lorch, Jochen H.; et al.
Abstract : Background: Merkel cell carcinoma (MCC) is a rare, aggressive skin cancer associated with poor survival outcomes in patients with distant metastatic disease (mMCC). In an initial analysis from JAVELIN Merkel 200, a phase 2, prospective, open-label, single-arm trial in mMCC, avelumab—a human anti–programmed death-ligand 1 (PD-L1) monoclonal antibody—showed promising efficacy and a safety profile that was generally manageable and tolerable. Here, we report the efficacy of avelumab after ≥1 year of follow-up in patients with distant mMCC that had progressed following prior chemotherapy for metastatic disease. Patients and methods: Patients received avelumab 10 mg/kg by 1-h intravenous infusion every 2 weeks until confirmed disease progression, unacceptable toxicity, or withdrawal. The primary endpoint was best overall response. Secondary endpoints included duration of response (DOR), progression-free survival (PFS), and overall survival (OS). Results: Patients ( N  = 88) were followed for a minimum of 12 months. The confirmed objective response rate was 33.0% (95% CI, 23.3%-43.8%; complete response: 11.4%). An estimated 74% of responses lasted ≥1 year, and 72.4% of responses were ongoing at data cutoff. Responses were durable, with the median DOR not yet reached (95% CI, 18.0 months-not estimable), and PFS was prolonged; 1-year PFS and OS rates were 30% (95% CI, 21%-41%) and 52% (95% CI, 41%-62%), respectively. Median OS was 12.9 months (95% CI, 7.5-not estimable). Subgroup analyses suggested a higher probability of response in patients receiving fewer prior lines of systemic therapy, with a lower baseline disease burden, and with PD-L1–positive tumors; however, durable responses occurred irrespective of baseline factors, including tumor Merkel cell polyomavirus status. Conclusions: With longer follow-up, avelumab continues to show durable responses and promising survival outcomes in patients with distant mMCC whose disease had progressed after chemotherapy. Trial registration: Clinicaltrials.gov identifier: NCT02155647 .